The Urgency of Integrated Circuit Layout Design Regulation in the Semiconductor Industry (Comparative Study of Indonesia and Japan): Urgensi Pengaturan Desain Tata Letak Sirkuit Terpadu Dalam Industri Semikonduktor (Studi Perbandingan Indonesia dan Jepang) - Baiquni, Muhammad Iqbal; Waspiah, Waspiah (Annual Review of Legal Studies, 2024)
The semiconductor industry plays an important role in the development of global technology, so the need for intellectual property rights protection for Integrated Circuit Layout Design (ICLD) is important. In Indonesia, regulations regarding ICLD still have weak protection for designers. This affects the low number of DTLST registration applications. Meanwhile, in Japan, the regulation of DTLST has mature and structured protection regulations for designers and business actors. This study uses a normative legal research method with a comparative approach and a statutory approach. The results of this study indicate that the DTLST Regulations in Indonesia and Japan have several similarities. However, there are differences between them; Definition of DTLST, Exclusive and Non-Exclusive Exploitation Rights, Reserve Engineering, Compensation Rights Regulations, Regulation of Institutional/Legal Entity Registration. DTLST is very important in the semiconductor industry, especially for IC Chips used in various electronic devices. Large investments in DTLST research and development drive innovation and efficiency in IC Chip production. Japan, with strict regulations and strong government support, has succeeded in increasing its semiconductor market. Japan's DTLST Law protects IPR through comprehensive regulations, in contrast to Indonesia which still faces weaknesses in Law No. 32 of 2000. The lack of substantive examination and understanding of technology in Indonesia hampers the effectiveness of legal protection. Based on this, it can be concluded that the regulation on DTLST in Indonesia still has several weaknesses and can seek to revise Law No. 32 of 2000 by transplanting laws from Japan with adjustments to Indonesia's national interests. Indonesia should strengthen legal protection of intellectual property rights for DTLST designers and business actors in the semiconductor industry.